Examining the Effects of Brief Mindfulness on Psychophysiological Responses and Performance in Self-Competitive Tasks - Noemí SanMiguel; Eva Laina-Vázquez; Diana Abad-Tortosa; Miguel Ángel Serrano (Applied Sciences)
Mindfulness practice has been recognized as an effective method for reducing stress, enhancing self-awareness, and improving overall well-being, influencing various cognitive processes such as attention and self-control. While extensive research has focused on long-term mindfulness programs, recent years have seen the emergence of brief mindfulness practices. This study aims to investigate the effects of brief mindfulness on electrophysiological responses, and performance in a self-competitive context. A total of 52 participants were divided into two groups for the experiment. They were randomly assigned to one of two experimental conditions: a brief mindfulness practice (n = 29) or a control intervention (n = 23), each lasting 10 min. Initially, participants completed a cognitive task (Tower of Hanoi—ToH), followed by their respective intervention. Participants then performed the ToH task again, with encouragement to exceed their previous performance. Measures were taken for performance metrics and psychophysiological responses—including electrodermal response (EDA) and cardiovascular parameters. The results indicated that a brief mindfulness significantly enhanced performance (p < 0.05), increased self-efficacy (including self-confidence and perceived task importance) prior to the ToH task, and reduced the perceived difficulty of the task upon completion. Moreover, an increase in EDA was found in the brief mindfulness group. However, no significant changes in the measured cardiovascular responses were observed. These findings suggest that brief mindfulness can effectively improve cognitive task performance by enhancing self-efficacy and reshaping task perception.